Maintenance and Rehabilitation Prioritization of School Buildings Using Knapsack Problem - Muhammad Abu Thohir; Senot Sangadji; Sholihin As'ad (International Journal of Science and Applied Science: Conference Series, 2017)
Many of the public buildings are in conditions of distress due to deterioration and damage and require maintenance and rehabilitation to be able to function appropriately. On the contrary the government funding and budget allocated is limited. A systematic approach to overcome the problem is using setting up priority and optimize the resources allocation. Within a budget ceiling the what buildings components should be prioritized to achieve maximum profit and or surpass threshold is the ultimate goal of the decision maker and stakeholders. In this study, optimizing budget allocated for maintenance and rehabilitation of building components may be carried out by implementing knapsack algorithm within dynamic programming framework. The public junior high school 4 (SMPN 4) building was chosen as case study to apply the algorithm and determine the priority scale. The building is in Salatiga and suffers from some material deterioration as well as structural component degradation. The school building consists of three main sections namely, building itself, school yard, and school fence. To assess and evaluate damage based on the criteria set by Ministry of National Education, the building is divide into structures, architecture, and utilities. These components were divided into elements and sub elements. The structure was divided into the roof structure, super structure above the ground, and substructure (foundation). The damage condition of components and sub components of the building was then tabulated by assigning weights according to criteria set by office of education of Salatiga (Dinas Pendidikan Kota Salatiga, 2017)